Photoperiodically sensitive and insensitive phases of preflowering development in rice - Yin, Xinyou; Kropff, Martin J.; Ynalvez, Marcus A. (Wiley, 1997)
The time interval between sowing and flowering in rice (Oryza sativa L.) comprises three successive phases: a basic vegetative phase (BVP), a photoperiod‐sensitive phase (PSP), and a post‐PSP phase (PPP). The objective of this study was to estimate the length of the three phases in diverse rice cultivars to provide the basis for accurately predicting rice flowering dates. In greenhouse experiments, plants of 20 cultivars were transferred from short day (SD) (10 h d−1) long day (LD) (12.5 or 14 h d−1) or from LD to at various tim es aft er sowing. The duration of BVP varied greatly among cultivars ranging from 16.7 to 45.4 d. The indica cultivars exhibited an apparently longer BVP than the japonica cuitivars. The duration of PPP also varied among cultivars, from 18.0 to 37.2 d. For all cultivars, the length of the intervening PSP was shorter under SD conditions (3.6–24.1 d) than under LD conditions (10.5–76.5 d); the difference in PSP between SD and LD depended on the photoperiod sensitivity of the cultivar. The PSP under both SD and LD conditions did not necessarily end at panicle initiation (PI), but, on average, 4 to 5 d after PI. This study confirms the necessity to divide the entire preflowering period into the three phases for modeling purposes. Further studies are needed to elucidate the phenomenoinn some cultivars of a significant delay of flowering by early SD‐to‐LD transfers before PI.